"Pigmented irritant contact dermatitis" − an issue of concern due to dithranol misuse in Andaman and Nicobar: an observational study - Pradeep Balasubramanian; Anjali J Anil (Wolters Kluwer Medknow Publications, 2020)
Background: Dithranol (anthralin) ointment is a topical medication that is widely being misused by the people in Andaman and Nicobar (A&N) that results in a characteristic irritant reaction. Aim of the study: This study was performed to analyze the various aspects pertaining to the irritant dermatitis due to dithranol misuse such as epidemiological aspects, clinical features, and management. Methodology: The study was done in the Outpatient Department of Dermatology of G.B. Pant Hospital, Port Blair, A&N. This study includes all the patients who presented with irritant reaction due to dithranol ointment and its combination, the clinical features, the common dermatoses in which it is being misused, source of usage (suggested by), and its management and measures undertaken to arrest its misuse. The variables are mentioned as frequency and percentage. Results: The dithranol irritant reaction was commonly seen in the setting of cutaneous dermatophyte infection. Groin was the common site affected. It was commonly encountered among male (76%) and in the age group of 21 to 40 years (75.9%). The medication was commonly suggested by the pharmacists. The "brown stain" due to dithranol was the classical feature seen in all the patients. Conclusion: This study lays emphasis on identifying the irritant reaction due to dithranol ointment through the characteristic "brown stain," the management of the condition, and the measures that had successfully reduced its misuse. Through the awareness imparted to the pharmacists and the general public, the misuse of the dithranol could be well curtailed in A&N.